Temporary employment as an alternative unemployement rate reducing new employment form analysis in Lithuania and Czech Republic - Svedaite, Erika; Tamosiunas, Teodoras (Univerzita Pardubice, 2012)
The paper study identify temporary employment as an alternative unemployment rate reducing new employment form in European Union, Lithuania and Czech Republic. After the scientific literature, European Labour Force Survey (EULFS), Eurostat, document and statistical department analysis, systematization and comparison there was presented temporary employment concept and how it reduce unemployment rate, legal this atypical work form regulation. A study disclosed temporary employment indicators and how it reduce unemployment rate in Lithuania, Czech Republic and European Union. Study provides results that show temporary employment importance in labor market that reduce unemployment rate.
Keywords: temporary employment; temporary work agency; temporary worker; temporary employment contract; temporary employment law; unemployment rate